Effectiveness of Grass-root Level Unit in Extension Delivery Services in Karnataka - A. Dympep and S. S.Dolli, (Indian Journal of Extension Education, 2016)
Timely and relevant access to information and input by farmers is necessary to improve agricultural productivity. Ademand driven extension system at the grass-root level called Raitha Samparka Kendras (RSKs) was established inKarnataka in the year 2000 replacing the earlier Training and Visit system (T&V). The study was conducted to analyse theeffectiveness of the extension services provided by RSKs in terms of its outreach to the farmers and its impact on theiragricultural production. Six RSKs of Gadag district of North Karnataka comprising of six Agricultural Officers (AO), 25Assistant Agricultural Officers (AAO) and 90 beneficiary farmers were selected. The study revealed that RSKs coveredwide geographical area and the ratio of extension personnel to farm families was high (1:1406). It was found that majority(85.56%) of the farmers' preferred to consult progressive farmers for agricultural information. No significant associationwas found between farmers' frequency of contact with their location from RSK as well as with their size of landholding.However, there was a significant association between the farmers' land holding and extension participation. Asignificantimpact was observed on yield of important crops after attaining the services from RSKs. Most of the farmers wereprimarily using RSK just as government retail outlet to buy subsidized agro-inputs rather than for attaining technicalagriculture information.